How Do Electronic Retailers’ Perceived Obstacles to Successful E-Commerce Differ With Regard To Search Goods and Experience Goods? - Schmidt, Axel (2010)
How do electronic retailers‟ („e-tailers‟) perceived obstacles to successful E-Commerce differ with regard to search goods and experience goods? To answer this research question, this qualitative, interpretive study made use of semi-structured interviews and contrasted the perceptions of the participating e-tailers‟ directors; a contact lenses and accessories company (search good case) and a stylish motorcyclists‟ protection clothes and accessories company (experience good case) in Switzerland. A theoretical framework was developed by merging two existent academic theories. Obstacle categories that were explored encompassed Trust and Credibility, Differentiators, Information Requirement, No Physical Touch, Loyalty, and Returns. Some prevalent propositions in academic literature were not reconfirmed. Markedly distinct perceptions were revealed with regard to Differentiators, No Physical Touch, and Loyalty. Based on the findings from an extensive literature review, the qualitative research, and an Internet search practical recommendations to e-tailers of Decorative Cosmetics – an experience good – were presented. The implementation of these recommendations might alleviate the online selling of experience goods by reducing online shoppers‟ uncertainty concerning their actual characteristics prior to the purchase. Future research could investigate the impact of contemporary multi-media web tools on uncertainty mitigation concerning the online purchasing of experience goods.